EVALUASI PEMBANGUNAN WILAYAH PENGEMBANGAN SELATAN DKI JAKARTA SEBAGAI KAWASAN RESAPAN AIR - Nugroho, Sutopo Purwo (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2002)
Southern Development Region DKI Jakarta is set as a water recharge area in the mean of decreasing the problem of water resources in DKI Jakarta. The fact, however, this rule does not run well, because there is not action plan and along with followed by development control and law enforcement. what that rule. Besides, the decree on Southern Develeopment Region as water recharging area is not optimal in either in groundwater stream point of view.That so, development in Southern Development Region must directed accomplishment with open space standard, park and playing field for city region, beginning of playlot, playground, playfield, and urban park. There is not only for old settlement, but new settlement development is necessary to put spatial arrangement in order.